Computational study of effect of transient fluid force on composite structures submerged in water - Y Kwon; S Knutton (International Journal of Multiphysics, 2016)
This study investigated the effect of the initial transient hydrodynamic loading on dynamic responses of composite structures which move under water from the rest condition to a steady-state velocity for a given time duration with different acceleration profiles. Numerical analyses were conducted including the fluid-structure interaction. The computational model was validated against an experimental data, and various cases were examined numerically. The cases include various transient velocities of the structure, fluid boundary conditions, structural geometric configurations and material properties. The results showed that the peak fluid pressure and the resultant stresses in the composite structures are dependent on most of those parameters significantly. The maximum stresses under transient hydrodynamic loading could be an order of magnitude larger than those stresses under the final steady-state loading. A lighter composite structure experienced greater stresses and strains while the fluid pressure did not have any noticeable change under the same flow condition.